PTU-215 Preferences for alternative haemorrhoid treatments: does type of treatment matter?. (22nd June 2015) - Kilonzo, MM; Krucien, N; Ryan, M; Watson, A
Abstract : Introduction: The treatment of haemorrhoids aims to relieve symptoms and improve quality of life. However, generic tools used to measure quality of life in economic evaluation may not be sensitive to patients' preferences for alternative treatment modalities and their associated outcomes. Discrete choice experiments (DCEs) are increasingly used in health economics as an alternative method to value health care. This technique can be used to investigate the tradeoffs that people are willing to make between different attributes of treatments. Method: Based on literature reviews and expert opinion, four important attributes of haemorrhoid treatment were identified: time in post operative pain; chance of serious complications requiring hospitalisation; time taken to return to usual activities; and chance of a recurrence of haemorrhoidal symptoms. Experimental design techniques were used to create a manageable number of choices between the alternative treatment modalities, which varied with respect to the levels ascribed to the treatment attributes and also a cost attribute, that was included to enable estimation of individuals' willingness to pay (WTP) for the different treatment modalities and attributes. The study was conducted using a sample of the general population from an online survey panel. Response data were analysed using conditional logistic regression techniques. Results: Of the 1010 respondents who completed the DCE, 44% had experienced haemorrhoids. Very few respondents chose not to be treated and none of the surgical treatment modalities were preferred over the others. The coefficients for all the attributes had the expected sign and were significantly different from zero (p < 0.0001). For example, an increase in chance of recurrence or the amount of time spent in pain was associated with a decrease in the probability of selecting an option. A marginal change in the chance of recurrence of haemorrhoidal symptoms had the greatest influence on respondents' choices, WTP for a percentage reduction in the chance of recurrence of haemorrhoidal symptoms and a percentage reduction in chance of serious complications was £189 and £117 respectively. Individuals were willing to pay £14 to reduce the time spent in post-operative pain by one day, and £14 to reduce the time taken to return to usual activities by one day. Conclusion: After accounting for the main associated attributes and outcomes of treatment, the type of treatment per se does not significantly influence patients' choices. The findings suggest that the outcomes of haemorrhoidal surgery influence the respondent choices and there is need for further research to put these findings into context by combining these results with evidence from randomised controlled trials to establish the most cost beneficial approach to treatment. Disclosure of interest: None Declared.